Revising the Impact and Prospects of Activity and Ventilation Rate Bio-Loggers for Tracking Welfare and Fish-Environment Interactions in Salmonids and Mediterranean Farmed Fish - Calduch-Giner, Josep; Holhorea, Paul George; Ferrer, Miguel Ángel; Naya-Català, Fernando; Rosell-Moll, Enrique; Vega García, Carlos; Prunet, Patrick; Espmark, Åsa M.; Leguen, Isabelle; Kolarevic, Jelena; Vega, Aurelio; Kerneis, Thierry; et al. (Frontiers in Marine Science, 2022)
Behavioral parameters are reliable and useful operational welfare indicators that yield information on fish health and welfare status in aquaculture. However, aquatic environment is still constraining for some solutions based on underwater cameras or echo sounder transmitters. Thus, the use of bio-loggers internally or externally attached to sentinel fish emerges as a solution for fish welfare monitoring in tanks- and sea cages-rearing systems. This review is focused on the recently developed AEFishBIT, a small and light data storage tag designed to be externally attached to fish operculum for individual and simultaneous monitoring of swimming activity and ventilation rates under steady and unsteady swimming conditions for short-term periods. AEFishBIT is a tri-axial accelerometer with a frequency sampling of 50–100 Hz that is able to provide proxy measurements of physical and metabolic activities validated by video recording, exercise tests in swim tunnel respirometers, and differential operculum and body tail movements across fish species with differences in swimming capabilities. Tagging procedures based on tag piercing and surgery procedures are adapted to species anatomical head and operculum features, which allowed trained operators to quickly complete the tagging procedure with a fast post-tagging recovery of just 2.5–7 h in both salmonid (rainbow trout, Atlantic salmon) and non-salmonid (gilthead sea bream, European sea bass) farmed fish. Dual recorded data are processed by on-board algorithms, providing valuable information on adaptive behavior through the productive cycle with the changing environment and genetics. Such biosensing approach also provides valuable information on social behavior in terms of adaptive capacities or changes in daily or seasonal activity, linking respiratory rates with changes in metabolic rates and energy partitioning between growth and physical activity. At short-term, upcoming improvements in device design and accompanying software are envisaged, including energy-harvesting techniques aimed to prolong the battery life and the addition of a gyroscope for the estimation of the spatial distribution of fish movements. Altogether, the measured features of AEFishBIT will assist researchers, fish farmers and breeders to establish stricter welfare criteria, suitable feeding strategies, and to produce more robust and efficient fish in a changing environment, helping to improve fish management and aquaculture profitability.